Employee Payroll Information System On Company Web-Based Consultant Engineering Services - Itsney Nur Hikmah; Muqorobin Muqorobin (Institut Teknologi Bisnis AAS Indonesia, 2020)
Consulting Engineering Services is a company engaged in building construction consulting services. In this company in processing employee salaries still use manual calculations and use the Ms. Excel program. This can lead to errors in calculating employee salaries and the process of printing employee salary slips which takes a long time. In solving this problem, the authors designed an employee payroll information system. In this design, the authors use the PHP programming language. The method in this research is the Waterfal Method. The method in this research is through observation, interview, documentation and literature study. The system design is made using Contex Diagram, HIPO, Input Output Design, relationships between tables and database design. The system is made in a program with the PHP programming language with a database format using MySQL. The result of this design is to produce an application program that will be used to process web-based employee salaries in CV. Consulting Engineering Services and it is hoped that companies will find it easier to input data and compile payroll reports to be faster and more efficient